Employee Engagement: A Theoretical Review - Harilal, A.; Santhosh , V. A. (Current Aspects in Business, Economics and Finance Vol. 6, 2022)
The idea of employee engagement is well-known. This article investigates the link between employee engagement and performance. Employee engagement has an impact on employee performance, which in turn has an impact on organisational performance. Additionally, it plays a crucial part in defining a variety of employee- and organization-related characteristics, such as job satisfaction, business outcomes, brand recognition, shareholder value, etc. Employee engagement varies between firms and is affected by a variety of internal and external factors. The engagement quotient of an employee is influenced by both internal and external factors of an organisation, including its policies, employee relations practices, and personality traits of the worker. The study gave a thorough analysis of the idea of employee engagement and connected it to other engagement-related criteria, recent developments, and its impact on performance.